A Systems Study on the Customer's Service Department of the Metropolitan Waterworks and Sewerage System - Albay, Fe Zinnia; Bautista, Gerard Paul; Castaneda, Claro; Legaspi, Rodolfo Jr; Mirabite, Josue; Mutuc, Jose Edgar; Perdigon, Virgilio S. Jr; Tan, Joel Nicolas; Varua, Gorgonia III (College of Engineering, 1984)
This study focuses on the Customer's Service Department of the Metropolitan Waterworks and Sewage System. It utilizes the Total Systems Approach. The Management Information System is accorded greater scrutiny than any other system within the CSD. A good measure of analysis involves Systems, Procedures and Methods. Data gathering from the CSD and related MWSS unites was conducted. Analysis and Design were done, sometimes concurrently with Data Gathering. Recommendations and Areas for Further Study were identified. In this report, Appendices are included to support the data within the study proper.